2013
DOI: 10.4021/jocmr1210w
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition in Critical Care

Abstract: There is a consensus that nutritional support, which must be provided to patients in intensive care, influences their clinical outcome. Malnutrition is associated in critically ill patients with impaired immune function and impaired ventilator drive, leading to prolonged ventilator dependence and increased infectious morbidity and mortality. Enteral nutrition is an active therapy that attenuates the metabolic response of the organism to stress and favorably modulates the immune system. It is less expensive tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 60 publications
0
39
0
12
Order By: Relevance
“…O débito energético acumulado é descrito como um forte preditor de desfechos clínicos, expondo os pacientes a deficit energéticos que, provavelmente, não serão compensados durante a internação nas Unidades de Terapia Intensiva 13,14 .…”
Section: N T R O D U ç ã Ounclassified
See 2 more Smart Citations
“…O débito energético acumulado é descrito como um forte preditor de desfechos clínicos, expondo os pacientes a deficit energéticos que, provavelmente, não serão compensados durante a internação nas Unidades de Terapia Intensiva 13,14 .…”
Section: N T R O D U ç ã Ounclassified
“…A resposta metabólica ao estresse associada à imobilidade prolongada e à oferta nutricional inadequada potencializam o catabolismo e predispõe o deficit nutricional 14,15 . Dessa forma, a adequação da oferta energético-proteica ao paciente crítico representa um importante desafio.…”
Section: N T R O D U ç ã Ounclassified
See 1 more Smart Citation
“…Lee et al [13] suggested that early enteral feeding is important predictor of outcome in acute severe brain injured patients. Enteral feeding in acute critically ill patients could provide the appropriate doses of macro-and micronutrients to meet the measured needs and modulate the inflammatory response [14]. However, there are few studies about the impact of enteral feeding in chronic severe brain injured patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the purpose of bettering the nutritional management, several various feeding methods have been tested [19,20]. Such management has two objectives to decrease the negative nitrogen balance and replace calorie and protein early.…”
Section: Nutritional Supportmentioning
confidence: 99%